2019
DOI: 10.1177/1359104519871335
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal body weight and food-related behavior in school-aged children as measured by the Children’s Binge Eating Disorder Scale

Abstract: Obesity in children is becoming a global epidemic. Health and emotional consequences can threaten life and health both during childhood and adulthood. In this study, we aimed to assess the coexistence of overweight and obesity, binge eating disorder and detrimental attitudes toward nutrition among school-age children. We also aimed to determine the usefulness of the Children’s Binge Eating Disorder Scale (C-BEDS) as a screening tool. We examined a group of over 550 healthy children aged 6–12. In all, 15% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…The percentage equalization of children with excess body weight in the control group and ADHD may result from several environmental factors that escalate from generation to generation (e.g., stress, the pace of life, easy access to relatively cheap and highly processed food). These, in turn, change eating habits and consequently lead to EBW in children not burdened with other developmental disorders [98]. The growing problem of overweight and obesity among children shows how important it is to discover genes that, on the one hand, create a predisposition to obesity and, on the other hand, are altered in expression under the influence of unfavorable environmental factors.…”
Section: Rare and Protein-truncating Variant (Ptv)mentioning
confidence: 99%
“…The percentage equalization of children with excess body weight in the control group and ADHD may result from several environmental factors that escalate from generation to generation (e.g., stress, the pace of life, easy access to relatively cheap and highly processed food). These, in turn, change eating habits and consequently lead to EBW in children not burdened with other developmental disorders [98]. The growing problem of overweight and obesity among children shows how important it is to discover genes that, on the one hand, create a predisposition to obesity and, on the other hand, are altered in expression under the influence of unfavorable environmental factors.…”
Section: Rare and Protein-truncating Variant (Ptv)mentioning
confidence: 99%
“…Dental and anthropometric examiners were thoroughly experienced researchers who had led similar subject measurements in several clinical studies [9,17,36]. The dentist (E.P.)…”
Section: Interview and Oral Examinationmentioning
confidence: 99%
“…In Poland, a similar trend was recorded among youth who were overweight or obese, from 17.8% to 21.9%, respectively [ 16 ]. A recent study by Dmitrzak-Weglarz et al reported that 78.5% of Polish school children had declared that they reached for snacks between meals [ 17 ]. This is consistent with previous studies that sweet snacks between meals were declared by 90% of children [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Para la evaluación del trastorno de atracones se han desarrollado diversas escalas como The Binge Eating Scale (16-SF) (BES); sin embargo, poco se ha estudiado sobre el atracón y su asociación directa con la diabetes tipo 2. 10,11…”
Section: Introductionunclassified